1997
DOI: 10.1046/j.1471-4159.1997.68010392.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase C‐α and Translocation of the Myristoylated Alanine‐Rich C‐Kinase Substrate Correlate with Phorbol Ester‐Enhanced Noradrenaline Release from SH‐SY5Y Human Neuroblastoma Cells

Abstract: Abstract:The aim of this study was to investigate the mechanism by which short-term pretreatment with the phorbol ester 1 2-O-tetradecanoylphorbol 13-acetate (TPA; 100 nM) enhances noradrenaline (NA) release from the human neuroblastoma cell line SH-SY5Y. Subcellular fractionation and immunocytochemical studies demonstrated that an 8-mm TPA treatment caused translocation of the rn-subtype of protein kinase C (PKC) from the cytosol to the plasma membrane. In contrast, TPA altered the distribution of PKC-c from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…When phosphorylated by activated PKC, MARCKS translocates from the plasma membrane to the cytoplasm. 24,25 Adler and co-workers showed that MARCKS is required for mucus secretion by human bronchial epithelial cells in culture. 26 MARCKSrelated peptide can therapeutically reduce mucus secretion in the airways of human patients with asthma, chronic bronchitis, and cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…When phosphorylated by activated PKC, MARCKS translocates from the plasma membrane to the cytoplasm. 24,25 Adler and co-workers showed that MARCKS is required for mucus secretion by human bronchial epithelial cells in culture. 26 MARCKSrelated peptide can therapeutically reduce mucus secretion in the airways of human patients with asthma, chronic bronchitis, and cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…MARCKS has been implicated in processes requiring signal-dependent changes in actin-membrane plasticity and cytoskeletal restructuring. 80,81 It can crosslink actin, bind calcium/ calmodulin, interact with the plasma membrane, and has been linked to organization of polyphosphoinositide (PI (4,5)P 2 ) signaling domains, 82,83 regulation of phospholipase D, 84 secretion, 85,86 and phagocytosis. 87 MARCKS is preferentially expressed in dendritic branches and axon terminals within limbic and limbic-associated regions of brain, as well as neuronal growth cones necessary for normal brain development.…”
Section: Lithium and Marcks: A Downstream Target For Pi/pkc Signalingmentioning
confidence: 99%
“…When phosphorylated by activated protein kinase C (PKC), MARCKS translocates from the plasma membrane to the cytoplasm (4,5). In previous studies in airway secretory cells, we demonstrated that MARCKS, upon phosphorylation, translocates to the cytoplasm, and there binds to membranes of intracellular mucin granules (2,3).…”
mentioning
confidence: 97%